Assessing the level of community participation as a component of community capacity building for tourism development - Aref, Fariborz; Redzuan, Ma’rof (Eurojournals, 2009)
Community participation is regarded as an important tool for successful tourism development. Western scholars generally agree that active community participation in the decision making process will benefit local communities. However, in developing countries, such as participation is difficult to put into practice due to shortcomings in structural, cultural and operational limitations in the tourism development process. A study was carried out to assess the level of community participation in tourism development. Community capacity building for tourism development requires a range of community participation. The paper is based on the study of community capacity building in tourism development which was carried in Shiraz city, Iran. The study found that the level of community participation generally was low and each district of Shiraz has different level of community participation in tourism development.